Multi-Trait Multi-Method Matrices for the Validation of Creativity and Critical Thinking Assessments for Secondary School Students in England and Greece - Ourania Maria Ventista (International Journal of Assessment Tools in Education)
The aim of this paper is the validation of measurement tools which assess critical thinking and creativity as general constructs instead of subject-specific skills. Specifically, this research examined whether there is convergent and discriminant (or divergent) validity between measurement tools of creativity and critical thinking. For this purpose, the multi-trait and multi-method matrix suggested by Campbell and Fiske (1959) was used. This matrix presented the correlation of scores that students obtain in different assessments in order to reveal whether the assessments measure the same or different constructs. Specifically, the two methods used were written and oral exams, and the two traits measured were critical thinking and creativity. For the validation of the assessments, 30 secondary-school students in Greece and 21 in England completed the assessments. The sample in both countries provided similar results. The critical thinking tools demonstrated convergent validity when compared with each other and discriminant validity with the creativity assessments. Furthermore, creativity assessments which measure the same aspect of creativity demonstrated convergent validity. To conclude, this research provided indicators that critical thinking and creativity as general constructs can be measured in a valid way. However, since the sample was small, further investigation of the validation of the assessment tools with a bigger sample is recommended.